2023
DOI: 10.3846/tede.2023.19821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CSR Implementation and Crisis Events in Business on the Financial Management of Smes

Ján Dvorský,
Ilona Švihlíková,
Ľudmila Kozubíková
et al.

Abstract: The financial management of a business is an integral part of strategic management. Small and medium-sized enterprises (SMEs) are vulnerable to the presence of crisis events in the business environment. In this context, senior managers and owners need to react promptly to emerging changes in a given business segment. The aim of the article is to quantify the effect of crisis events in business and firm’s CSR implementation in business on the financial performance in the SMEs. The empirical research incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Authors also found that CSR implementation had stronger effect on the sustainability of SMEs in Czech enterprises than Slovak enterprises. Dvorský et al (2023a) on the base of case study of 1,090 SMEs from the business environment Visegrad group countries showed that did not confirm the negative effects of crisis events in business on the financial management, but level of implementation CSR is significant in the context of corporate sustainability.…”
Section: H4: Applying Ethics In Business Has a Positive Effect On The...mentioning
confidence: 93%
“…Authors also found that CSR implementation had stronger effect on the sustainability of SMEs in Czech enterprises than Slovak enterprises. Dvorský et al (2023a) on the base of case study of 1,090 SMEs from the business environment Visegrad group countries showed that did not confirm the negative effects of crisis events in business on the financial management, but level of implementation CSR is significant in the context of corporate sustainability.…”
Section: H4: Applying Ethics In Business Has a Positive Effect On The...mentioning
confidence: 93%
“…Moreover, it highlights the impact of external events such as the pandemic, ongoing conflicts between Russia and Ukraine, and increasing inflation. All these reflect the impact on SMEs' sustainability (Dvorský et al, 2023a;Dvorský et al, 2023b;Semenikhina et al, 2023). They must adopt necessary considerations and safeguard themselves from turbulence and other critical factors in the current economic environment.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…As they are small businesses, their functioning depends mainly on the attitudes of owners and managers. The two most influential factors in future business are the view of financial risk as a positive indication of financial accomplishment and a normal component of a company's operations (Dvorský et al, 2023b). Efficient financial processes and risk management can support the sustainability of businesses.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Sustainability primarily consists of three pillars: environmental, economic and social. Several adjectives, such as 'ecological', 'green' and 'blue', can also be found in the literature (Álvarez Jaramillo et al, 2019;Matuszewska-Pierzynka, 2021;Kowalska & Bieniek, 2022;Dvorský et al, 2023;Balcerzak et al, 2023).…”
Section: Sustainable Development Of Smesmentioning
confidence: 99%